Effect of melamine phosphate on the thermal stability and flammability of bio-based polyurethanes. Issue 1 (January 2016) - Yakushin, Vladimir; Sevastyanova, Irina; Vilsone, Dzintra; Avots, Andris
Abstract: The effect of melamine phosphate (MP) on the thermal stability of bio-based polyurethane and the flammability parameters of wood samples with polyurethane coatings was studied. Thermogravimetric analysis and cone calorimeter test at a heat flux of 35 kW/m 2 were used for this purpose. The main characteristics of the thermal stability and flammability of the coating with addition of MP were compared with the characteristics of analogous coatings with addition of ammonium polyphosphate (APP), as well as APP in combination with melamine. It was found that the use of MP as an intumescent additive allows a considerable decrease of most of the flammability parameters of the polyurethane based on tall oil fatty acids, like APP. To reach the maximum effect, it is enough to load in the polyurethane 20% of MP. In contrast to APP, MP reduces also the smoke release of the samples. Using MP in combination with APP at definite weight ratios, it is possible to essentially reduce the flammability parameters of polyurethane coatings, such as PHRR, THR and MARHE.